ChemInform Abstract: Site‐Selective Synthesis of Arylated Pyridines by Suzuki—Miyaura Reactions of 2, 3, 5, 6‐Tetrachloropyridine. Issue 46 (November 2015) - Reimann, Sebastian; Ehlers, Peter; Parpart, Silvio; Surkus, Annette; Spannenberg, Anke; Langer, Peter
Abstract The site selective mono‐, di‐ and triarylation of 2, 3, 5, 6‐tetrachloropyridine is described.